56 is 69% of what number? Round your answer to the nearest hundredth if necessary.Incorrect answer:124

Answers

Answer 1
Answer:

Answer:

Approximately 81.159

Step-by-step explanation:

First, set up the equation

56    =   (0.69)(x)

       ^ is 69% of a number

Divide each side by 0.69 to simplify

56 / 0.69 = x

x ≈ 81.159420...


Related Questions

the lenghtvof each side of a square is 2.5 meter. if each side is doubled in length, what is the effect on the perimeter of the square? a.it remain the same b.it is one half the original perimeter c. it is four time the original perimeter d. it is twice the original perimeter.
On a local sports​ team, 80​% of 25 players are right​-handed. How many right​-handed players are​ there?
F is the mid point of EG . If EF = 5x and EG = 7x + 5, what is EG?
Karyn cuts the length of a ribbon into 4 equal pieces. each 1 1/4 feet long. How long was the ribbon?
The price of a pair of shoes is $28. The sales tax rate is 2.39 percent. What is the total amount you would pay if you bought these shoes?

a culture initially contains 200 bacteria . if the number of bacteria doubles every 2 hours , how many bacteria will be in the culture at the end of 12 hours ?

Answers

The population of the bacteria that doubles every 2 hours and have 200 initial population within 12 hours is 12,800. This is computed by dividing 12 hours by 2 hours, which will give us 6. This means that the bacteria doubled six times. Thus, multiplying 200 by 2 six times, this will give us 12,800.
So after every 2 hours the bacteria's numbers double (or 100% is "added") so we can simplify 12 down to 6 because we only want the number after every two hours, 400+800+1600+3200+ 6400+ 12800 = 25200 total after 12 hours

At Southside Middle School, 20% of the students play an instrument. There are 305 students. How many students play an instrument?/

Answers

Answer:

61 students

Step-by-step explanation:

When finding the percentage of a number, you can simply cross multiply and divide:

we can remove the percentage symbol…

20*305=\n 6100

Now 6100 divided by 100 is:

61

hope this helps!

H(t) = -5t^2+20t+1 what time does the ball reach the same height it was kicked at again? When does the ball reach its max height? What is the max height?

Answers

h(t) = -5t² + 20t + 1
-5t² + 20t + 1 = 0
t = -(20) +/- √((20)² - 4(-5)(1))
                      2(-5)
t = -20 +/- √(400 + 20)
                  -10
t = -20 +/- √(420)
              -10
t = -20 +/- 2√(105)
              -10
t = -20 + 2√(105)      t = -20 - 2√(105)
             -10                           -10
t = 2 - 0.2√(105)      t = 2 + 0.2√(105)
h(t) = -5t² + 20t + 1
h(2 - 0.2√(105)) = -5(2 - 0.2√(105))² + 20(2 - 0.2√(105)) + 1
h(2 - 0.2√(105)) = -5(2 - 0.2√(105))(2 - 0.2√(105)) + 20(2) - 20(0.2√(105)) + 1
h(2 - 0.2√(105)) = -5(4 - 0.4√(105) - 0.4√(105) + 0.04√(11025)) + 40 - 4√(105) + 1
h(2 - 0.2√(105)) = -5(4 - 0.8√(105) + 0.04(105)) + 40 + 1 - 4√(105)
h(2 - 0.2√(105)) = -5(4 - 0.8√(105) + 4.2) + 41 - 4√(105)
h(2 - 0.2√(105)) = -5(4 + 4.2 - 0.8√(105)) + 41 - 4√(105)
h(2 - 0.2√(105)) = -5(8.2 - 0.8√(105)) + 41 - 4√(105)
h(2 - 0.2√(105)) = -5(8.2) - 5(-0.8√(105)) + 41 - 4√(105)
h(2 - 0.2√(105)) = -41 + 4√(105) + 41 - 4√(105)
h(2 - 0.2√(105)) = -41 + 41 + 4√(105) - 4√(105)
h(2 - 0.2√(105)) = 0 + 0
h(2 - 0.2√(105)) = 0
(t, h(t)) = (2 - 0.2√(105), 0)
or
h(t) = -5t² + 20t + 1
h(2 + 0.2√(105)) = -5(2 + 0.2√(105))² + 20(2 + 0.2√(105)) + 1
h(2 + 0.2√(105)) = -5(2 + 0.2√(105))(2 + 0.2√(105)) + 20(2) + 20(0.2√(105)) + 1
h(2 + 0.2√(105)) = -5(4 + 0.4√(105) + 0.4√(105) + 0.04√(11025)) + 40 + 4√(105) + 1
h(2 + 0.2√(105)) = -5(4 + 0.8√(105) + 0.04(105)) + 40 + 4√(105) + 1
h(2 + 0.2√(105)) = -5(4 + 0.8√(105) + 4.2) + 40 + 1 + 4√(105)
h(2 + 0.2√(105)) = -5(4 + 4.2 + 0.8√(105)) + 41 + 4√(105)
h(2 + 0.2√(105)) = -5(8.2 + 0.8√(105)) + 41 + 4√(105)
h(2 + 0.2√(105)) = -5(8.2) - 5(0.8√(105)) + 41 + 4√(105)
h(2 + 0.2√(105)) = -41 - 4√(105) + 41 + 4√(105)
h(2 + 0.2√(105)) = -41 + 41 - 4√(105) + 4√(105)
h(2 + 0.2√(105)) = 0 + 0
h(2 + 0.2√(105)) = 0
(t, h(t)) = (2 + 0.2√(105), 0)

If (-3, y) lies on the graph of y = 3-x, then y =

-27
1/27
27

Answers

sub
(x,y)
(-3,y)
x=-3
y=y
y=3-(-3)
y=3+3
y=6

y=6 which is mysteriously not listed

you're going to want to pick

B. 1/27

because

y=3^-3

y=1/(3^3)

y=1/(3 x 3 x 3)

y=1 / 27

i have no clue how this guy got Verrified answer

its a 3 choice question on odyssey ware.

we didn't make it man

Can 39/121 be simplified and if so what is it??

Answers

Hi there!


Unfortunately, the beautiful fraction you've given us is simplified enough, and it cannot go any lower than what it is. So basically, you're left with (39)/(121)


Hope this helps!

Message me if you need anything else! I'd be happy to help! :D

Three candidates: A, B, C. Candidate A received 20% of the votes, while candidate B received exactly 3 times as many votes as candidate C. What percentage of votes did candidate C receive? a) 10% b) 15% c) 20% d) 5%

Answers

Answer: C received 20% of the votes so C would be your answer

Answer:

Step-by-step explanation:

Let C received x% votes. Then B received 3x% votes. B and C together received 80% of votes because A received the remaining 20%.

x + 3x = 80

4x = 80

x = 20

Answer: c) 20%